Influence of Soil Moisture on Absorption, Translocation, and Metabolism of Florpyrauxifen-benzyl. Issue 4 (7th June 2018) - Miller, M. Ryan; Norsworthy, Jason K.
Abstract: Florpyrauxifen-benzyl is a new active ingredient that represents an additional tool in rice ( Oryza sativa L.) weed control by providing an alternative mechanism of action. Studies were conducted to evaluate soil moisture influences on florpyrauxifen-benzyl absorption, translocation, and metabolism in three problematic weeds. In the absorption/translocation study, barnyardgrass [ Echinochloa crus-galli (L.) P. Beauv.], hemp sesbania [ Sesbania herbacea (Mill.) McVaugh], and yellow nutsedge ( Cyperus esculentus L.) were treated with [ 14 C]florpyrauxifen-benzyl under two soil moisture regimes (7.5% and 60% field capacity). Greater absorption occurred under moist conditions (60% soil moisture content). More translocation of the herbicide to the area above the treated leaf occurred under moist versus dry soil across all weed species. Sesbania herbacea translocated 25% of the absorbed herbicide above the treated leaf, a result greater than that of the other two weed species at 60% soil moisture. However, no differences in translocation occurred among the weed species at the 7.5% soil moisture regime. In the metabolism study, 95% of the herbicide recovered was in its acid form under the high soil moisture regime for S. herbacea, a species that shows extreme sensitivity to even low doses of this herbicide, and soil moisture influenced the amount of acid form found in all species. While these data provide a limited view into the physiological processes being affected, they do suggest that for E. crus-galli, S. herbacea, and C. esculentus, soil moisture content in the field will likely play a significant role in absorption, translocation, and metabolism of florpyrauxifen-benzyl.